The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2174/1389201020666190722161004
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and in-vitro Investigation of Polycaprolactone - (Polyvinyl Alcohol/Collagen) Hybrid Nanofiber as Anti-Inflammatory Guided Tissue Regeneration Membrane

Abstract: Background: Periodontal disease is the most common oral condition that affects the tissue surrounding the teeth. The oral cavity is colonized by an impressive array of micro-organisms, many of which can colonize the implants such as Guided Tissue Regeneration (GTR) often utilized in recovering procedures that result in inflammation interfering with the bone regeneration. Methods: In the current study, a nano-hybrid GTR membrane is developed as a heliacal structure scaffold with localized drug delivery funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…23,24 PCL is widely used in the fields of drug carriers, plasticizers, degradable plastics, nanofiber spinning, and molding materials. [25][26][27] Many methods have been utilized to prepare wound dressing, including stretching, template synthesis, molecular spinneret spinning, electrospinning, and so on. 5 Among them, electrospinning has become an effective method for the direct and continuous preparation of nanofibrous membranes owing to its simple operation and conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 PCL is widely used in the fields of drug carriers, plasticizers, degradable plastics, nanofiber spinning, and molding materials. [25][26][27] Many methods have been utilized to prepare wound dressing, including stretching, template synthesis, molecular spinneret spinning, electrospinning, and so on. 5 Among them, electrospinning has become an effective method for the direct and continuous preparation of nanofibrous membranes owing to its simple operation and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Polycaprolactone (PCL) has good biocompatibility, mechanical properties, and biodegradability, and it can improve the mechanical properties of composite electrospinning membranes to adapt to irregular wound contours 23,24 . PCL is widely used in the fields of drug carriers, plasticizers, degradable plastics, nanofiber spinning, and molding materials 25–27 …”
Section: Introductionmentioning
confidence: 99%
“…Two peaks at 2866 and 2939 cm −1 can be related to the symmetric vibration of CH 2 . Asymmetric stretching of COC appeared at 1165 and 1238 cm −1 [23]. The spectrum of PVA shows a broad peak in the range of 3200-3550 cm −1 related to the hydrogen bond of PVA.…”
Section: Chemical Characterization Of Nanofibersmentioning
confidence: 96%
“…However, for PVA, a 7% increase in the concentration of the polymer results in a nozzle drop without any electrospun nanofibers. Studies have shown that the best PVA concentration for electrospinning is 7%, and above that concentration, electrospinning power decreases [23]. For collagen, concentrations of 60 and 70% were investigated, and collagen 70% showed less clot than collagen 60%.…”
Section: Clotting Of the Nozzle Headmentioning
confidence: 99%
“… Type of scaffold Anti-inflammatory component Research design Experimental duration Induction of inflammation Outcomes Ref CS/PVA/HA electrospun fibers and films Meloxicam (NSAIDs) In vitro material characterization; cytocompatibility test (VERO cell culture) 72 h N/A Meloxicam, a selective COX-2 inhibitor, showed a sustained drug release over extended periods of time from CS/HA/PVA composite fibrous membranes and films; no direct observation in ant-inflammatory effect [ 63 ] Electrospun polycaprolactone (PCL) scaffold Ibuprofen (IBU) In vitro material characterization; cell vitality & wound closure assay, release profile, and in vivo periodontal regeneration evaluation 22 days LPS The anti-inflammatory effects of IBU on gingival cells were actively intensified; IBU-PCL scaffold significantly enhanced the clinical attachment and reduced bone destruction in mouse model. [ 65 ] 3D BMP-2-Delivering Tannylated polycaprolactone (PCL) Scaffold Tannic acid (TA) In vitro material characterization; release profile; antioxidant assay; ROS measurement; anti-inflammatory effect test; ALPase activity assay 28 days LPS The BMP-2/TA/PCL scaffold significantly inhibited the mRNA levels of MMP-3, COX-2, IL-6, and TNF-α in LPS; increased osteogenic effect [ 66 ] Polycaprolactone - (Polyvinyl Alcohol/Collagen) Hybrid Nanofiber Ibuprofen (IBU) In vitro material characterization; release profile N/A N/A Both PCL and PVA/COL loaded membranes consistently released IBU; no direct observation in ant-inflammatory effect [ 67 ] Collagen membrane Progranulin (PGRN) In vitro coimmunoprecipitation assay; in vivo periodontal regeneration evaluation by microCT analysis, histomorphometric analysis & immunohistochemical staining …”
Section: Purpose Of Use Of Biomaterials Scaffolds For Periodontal Regementioning
confidence: 99%